2020
DOI: 10.1093/geront/gnaa178
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Break: Daily Respite Effects of Adult Day Services as Objective and Subjective Time Away From Caregiving

Abstract: Background and Objectives Adult day services (ADS) can provide emotional and physical relief for caregivers of persons with dementia. While prior studies conceptualized ADS use at the aggregate level as a dichotomous construct, little is known about objective and subjective respite as distinct constructs. This study investigated how objective and subjective breaks from caregiving were associated with caregivers’ daily emotional well-being. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Importantly, this study found that caregiver distress overnight was buffered by ADS use, which provided time away from caregiving in the daytime (Wylie et al, 2021). On days when persons with ADRD used ADS, caregivers perceived BPSD as less stressful at nighttime.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Importantly, this study found that caregiver distress overnight was buffered by ADS use, which provided time away from caregiving in the daytime (Wylie et al, 2021). On days when persons with ADRD used ADS, caregivers perceived BPSD as less stressful at nighttime.…”
Section: Discussionmentioning
confidence: 94%
“…ADS is beneficial to family caregivers by reducing their exposure to daily BPSD by up to 40% and caregivers' distress associated with BPSD in the daytime (Vandepitte et al, 2016;Zarit et al, 2011Zarit et al, , 2014. Indeed, on average, caregivers reported 7.12 respite hours when their relatives used ADS, compared to 1.74 respite hours when they were at home with persons with ADRD (Wylie et al, 2021). For persons with ADRD, attending ADS during the day may also help reduce sundown syndrome, possibly because it can help better engage persons with ADRD in social and physical activities compared with a non-ADS day when the persons with ADRD stay at home (Woodhead et al, 2005;Yevchak et al, 2012), and perhaps provide more exposure to daylight (Ancoli-Israel et al, 2003;Gnanasekaran, 2016).…”
Section: Contributing Factors To the Daily Bpsd Fluctuation And Appra...mentioning
confidence: 99%
“…Indeed, socialization and social support are defining elements of ADS and caregiver respite has been found to be one of the more effective services offered by ADS centers. 20 ADS would be well served to focus on these outcome domains as the resulting data could paint a more complete picture.…”
Section: Discussionmentioning
confidence: 99%
“…These are key functions of home and community‐based services and such services “can decrease unnecessary medical services utilization, delay institutionalization, and improve the quality of life of both patients with ADRD and their caregivers.” 19 This is not to say that ADS centers do not provide these services; rather, they may not be reporting this data. Indeed, socialization and social support are defining elements of ADS and caregiver respite has been found to be one of the more effective services offered by ADS centers 20 . ADS would be well served to focus on these outcome domains as the resulting data could paint a more complete picture.…”
Section: Discussionmentioning
confidence: 99%